Levantamiento de procesos del sistema de gestión del aseguramiento de la calidad de la Universidad Técnica de Cotopaxi. - Analuisa Analuisa, Erika Elizabeth (2023)
The present research arises from the necessity of defining processes while maintaining a quality system for Higher Education institutions, which must always keep up for continuous improvement. To achieve this, the objective is to perform a process analysis of the Quality Assurance Directorate at the Technical University of Cotopaxi using specialized workflow design software. In the methodological section, a quantitative approach was employed, based on processes already defined in the SiGAC indicator matrix, which provides data for an initial mapping of flowcharts based on their indicators. We establish to follow the theoretical framework of standard process analysis systems defining the collection of information through pre-analyzed process sheets that were modified and adapted according to needs. These sheets serve as guidelines for directors to define and validate the processes and indicators. Besides, flowcharts were created according to the proposed methodology using the modeling software Bizagi Modeler. The respective processes of different areas were established, along with validation of these processes. Validation is based on completed sheets reviewed by different department heads and the flowcharts that demonstrate how these processes operate to achieve the outcomes that reach the Quality Assurance Department. Finally, the research work makes it possible to trace processes from their beginning to keep up validation. This contributes to the improvement and optimization of processes within the Integrated Quality Assurance Management System of the Technical University of Cotopaxi.